The Tempest - Shakespeare, William frey50; Wright, Louis B.; LaMar, Virginia A. (Washington Square Press, Inc. New York, 1961)
Contains the text of the play, information about Shakespeare and his theater, bibliography, key to famous lines and phrases, and explanatory notes.
Keywords: Shakespeare, William -- 1564-1616 -- Plays; Drama